Highly sensitive detection of sentinel lymph node metastasis of breast cancer by digital PCR for RASSF1A methylation - Abe, Mizuho (Oncol Rep, 2019)
One-step nucleic acid amplification (OSNA) targeting cytokeratin 19 (CK19) mRNA expression and pathological examination are widely used for the intraoperative diagnosis of sentinel node (SN) metastasis. The aim of the present study was to develop a novel assay for detecting SN metastasis by targeting Ras association domain-containing protein 1 (RASSF1A) methylation in tumor cells, and to compare its performance with OSNA. Using digital PCR with methylation-specific restriction enzymes (RE-dMSP), our assay was able to detect ≥3 copies of methylated DNA per well, and was ≥10 times more sensitive than real-time PCR with bisulfite modification. OSNA lysates were examined using RE-dMSP and digital PCR for PIK3CA mutation, in the event that primary tumors were PIK3CA mutation-positive. RE-dMSP revealed a high concordance of 95.0% (153/161) with OSNA, and 100% (59/59) with PIK3CA mutation for detecting SN metastasis. In 11 breast cancer cell lines, the variation in methylated RASSF1A copy number was significantly lower than that of CK19 mRNA (2.8 vs. 10.5-fold; P<0.01). RE-dMSP has the potential to more accurately detect SN metastasis, and to more precisely estimate total tumor loads in SN, compared with OSNA.